2018
DOI: 10.3389/fonc.2018.00367
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Vascular Endothelium as Decision Maker in Cancer Therapy

Abstract: Genetic and pathophysiologic criteria prearrange the uncontrolled growth of neoplastic cells that in turn initiates new vessel formation, which is prerequisite for further tumor growth and progression. This first endothelial lining is patchy, disordered in structure and thus, angiogenic tumor vessels were proven to be functionally inferior. As a result, tumors were characterized by areas with an apparent oversupply in addition to areas with an undersupply of vessels, which complicates an efficient administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 111 publications
(130 reference statements)
6
125
0
3
Order By: Relevance
“…65 The findings of our study are timely as vascular normalization is quickly becoming an attractive therapeutic strategy. 31,66,67 Dual targeting of both ANG2 and VEGFA signaling has demonstrated efficacy in pre-clinical animal models of breast cancer, colon cancer, and glioblastoma. [68][69][70] ANG2 itself is an attractive therapeutic target as studies have shown that inhibition of ANG2 signaling decreases tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…65 The findings of our study are timely as vascular normalization is quickly becoming an attractive therapeutic strategy. 31,66,67 Dual targeting of both ANG2 and VEGFA signaling has demonstrated efficacy in pre-clinical animal models of breast cancer, colon cancer, and glioblastoma. [68][69][70] ANG2 itself is an attractive therapeutic target as studies have shown that inhibition of ANG2 signaling decreases tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor vasculature is a key mediator of lymphocyte exclusion whereby the vessels themselves can impede leukocyte tethering and subsequent extravasation into tumor tissues. 25,30,31 Due to the T cell exclusion observed in metastatic OS ( Figure 5), we focused our attention towards further investigating the relationship between vascular function and lymphocyte abundance. E-selectin, encoded by the SELE gene, is an endothelial cell adhesion molecule that facilitates leukocyte tethering and rolling on the vascular wall, the first step in [32][33][34] Whereas ICAM1 and PECAM1 can be expressed in both endothelial cells and tumor cells, SELE is expressed exclusively in endothelial cells and is transcriptionally upregulated in response to inflammation, thus serving as a marker of an activated and functional endothelium.…”
Section: Assessment Of the Tumor Vasculature In Metastatic And Non-mementioning
confidence: 99%
“…However, the endothelial cells that line these new vessels have lower than normal expression of endothelial adhesion molecules, such as intercellular adhesion molecules 1 and 2, vascular cell adhesion molecule 1, E-selectin, and CD34 (94). This endothelial anergy, characterized as unresponsiveness to inflammatory signaling, results in decreased adhesion of immune cells to the wall of the vessel, leading to reduced effector T-cell infiltration into the tumor, which is a key mechanism of immune evasion of solid malignancies (95).…”
Section: Role Of Cell Adhesion Molecules In the Tumor Microenvironmentmentioning
confidence: 99%
“…Herein, the tumor microenvironment is increasingly recognized not just as a growth-supporting tumor compartment but as a key determinant of radiation therapy (RT) resistance [13][14][15][16] . Among the cell types within the tumor-stroma, ECs were shown to be critical determinants of the radiation response of tumors 9,[17][18][19][20] . IR exposure induced acute vascular damage and EC apoptosis, leading to severe EC loss finally resulting in vascular dysfunction 17,[20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Among the cell types within the tumor-stroma, ECs were shown to be critical determinants of the radiation response of tumors 9,[17][18][19][20] . IR exposure induced acute vascular damage and EC apoptosis, leading to severe EC loss finally resulting in vascular dysfunction 17,[20][21][22] . Mechanistically, the p38 MAPK signaling pathway is essential for the EC response to stress stimuli including IR 23 .…”
Section: Introductionmentioning
confidence: 99%